The Effect of Service Quality Dimensions, Perceived Value, Customer Satisfaction, and Brand Love toward Customer Retention on First Media’s Subscribers - Irwanto Halim; Margaretha Pink Berlianto (Universitas Bina Sarana Informatika, 2024)
In the dynamic telecommunications sector, customer retention is of paramount importance for companies like First Media in Indonesia, given the rapid technological advancements and increasing demand for high-quality services. This study explores the factors influencing customer retention, including service encounter communication, internet service quality, service convenience, perceived value, customer satisfaction, and brand love. Service encounter communication, service convenience, and internet service quality are examined in relation to their effect on perceived value, customer satisfaction, and customer retention. A comprehensive survey was conducted using Google Forms, with 49 indicators distributed across these variables, and data analysis was performed with 313 samples using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results indicate that service encounter communication has a positive and significant effect on perceived value, customer satisfaction, and customer retention. Service convenience positively affects customer satisfaction but does not affect perceived value or customer retention. Internet service quality has a positive influence on perceived value. Perceived value enhances customer satisfaction, leading to improved customer retention and brand love, which in turn positively influences customer retention. This study provides valuable insights for First Media to enhance customer retention and satisfaction. However, it has limitations in terms of variable selection and testing, suggesting opportunities for future research to explore additional factors contributing to customer retention and brand management.